The complete chloroplast genome of Lilium paradoxum Stearn (Liliaceae) from southwestern China - Li Luan; Yu-Mei Yuan; Yue-Liang Jiang; Yu-Xi Wang; Jian-Hua Ma; Qiao-Ling He; Yun-Dong Gao (Mitochondrial DNA. Part B. Resources)
Lilium paradoxum, a herb from southeastern Xizang, China, has its first complete chloroplast genome sequenced using next-generation sequencing. The genome is 151,814 bp, consisting of inverted repeats (IRs; 26,323 bp), small single-copy (SSC; 17,524 bp), and large single-copy regions (LSC; 81,644 bp). It encodes 112 unique genes: 78 protein-coding, 30 tRNA, and 4 rRNA genes. Phylogenetic analysis of 22 genomes shows L. paradoxum is closely related to L. gongshanense, L. apertum, and L. souliei. These findings enhance understanding of Lilium's phylogenetic relationships and evolution, particularly the Nomocharis clade in the Hengduan Mountains.